2001
DOI: 10.1007/s002440010265
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Effect of Taurine Against Lead-Induced Oxidative Stress

Abstract: Abstract. Oxidative stress is proposed as a molecular mechanism in lead toxicity, which suggests that antioxidants might play a role in the treatment of lead poisoning. The present study was designed to investigate whether taurine has a beneficial effect both on Chinese hamster ovary (CHO) cells and on Fisher 344 (F344) rats following lead exposure. Therefore, oxidative stress parameters (glutathione, malondialdehyde levels, catalase, and glucose-6-phosphate dehydrogenase [G6PD] activities) of lead-exposed CHO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
73
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 139 publications
(77 citation statements)
references
References 33 publications
4
73
0
Order By: Relevance
“…Lead, among the heavy metals, threatens animal and human lives through air and food cycle. Lead toxication has been reported to adversely affect several systems and cause oxidative stress (Gurer et al, 2001). Kefir, one of the fermented milk products, is counted as an essential probiotic.…”
Section: Introductionmentioning
confidence: 99%
“…Lead, among the heavy metals, threatens animal and human lives through air and food cycle. Lead toxication has been reported to adversely affect several systems and cause oxidative stress (Gurer et al, 2001). Kefir, one of the fermented milk products, is counted as an essential probiotic.…”
Section: Introductionmentioning
confidence: 99%
“…Results obtained from our previous studies of CHO cells (Yusof et al, 1999;Gurer et al, 1998Gurer et al, , 1999aGurer et al, , 1999bGurer et al, , 2001Neal et al, 1999) with CHO cells showed that lead induces oxidative stress and that this can be reversed by numerous well-known antioxidants, including N-acetylcysteine, taurine, and captopril (Yusof et al, 1999;Gurer et al, 1998Gurer et al, , 1999aGurer et al, , 1999bGurer et al, , 2001Neal et al, 1999). Therefore, we used the same cell line to evaluate the effects of SeCys on lead-induced oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulated evidence of lead's capacity to induce oxidative stress suggests that lead toxicity may be mitigated by improving the cellular availability of antioxidant agents [1]. It has been proposed that usage of an antioxidant compound in the presence of a chelator will improve the efficacy of the lead poisoning treatment [1,5]. Hence, it can be presumed that natural compounds with both chelating and antioxidant activities could be good candidates for mitigating adverse effects of lead [2,5,6].…”
Section: Introductionmentioning
confidence: 99%